Variation and Phenetic Relationship of Tobacco (Nicotiana tabacum L.) In Central Java and Yogyakarta Based on Morphological Characters - Santoso, Agung Dwi; Purnomo, Purnomo (Jurnal Riset Biologi dan Aplikasinya, 2021)
Tobacco (Nicotiana tabacum L.) is a plant used as a mixture of cigarettes, and recreational media especially for men. This study aimed to identify variations, and determine the relationship between tobacco cultivars in Central Java and Yogyakarta based on macromorphological and micromorphological characters. Sampling locations are determined by surveying locations in both regions. Tobacco samples found include 5 cultivars in Central Java namely 'Mantili', 'Uler Magetan', 'Garut', ‘Gober Boyolali’, 'Manila', and 3 cultivars in Yogyakarta namely 'Siluk', 'Java', and 'Virginia'. Characterization with 23 qualitative macromorphological characters including leaves, and stems, with 9 qualitative and quantitative micromorphological characters including trichome and stomata. Descriptive data analysis is done to obtain the typical character of each cultivar, followed by numerical analysis including scoring characters processed with MVSP (Multi Variate Statistical Package), clustering with UPGMA (Unweighted Pair Group Method with Averages), and calculation of similarity coefficients with Simple matching formula. The results showed variations in the macromorphological characters including the shape of the leaf lamina, the base of the leaf, the absence of leaf stalks, and type of leaf venation. Tobacco has anisositic stomata, and varies in terms of length, width, and density of stomata. Tobacco trichomes are glandular. The result dendrograms form two clusters (A and B) with the similarity index of each cluster above 0.80. Cultivars with close relationships such as 'Siluk'-'Java', and far relationship like 'Java'-'Manila'.